Physiological, environmental, and life-history drivers of haemosporidian infections in non-passerine birds from a rehabilitation center - Vieira, Lis Marques de Carvalho e; Aguiar de Souza Penha, Victor; McGraw, Kevin J.; da Silva, Amanda Vitória Dornelas; Braga, Erika Martins (Frontiers in Parasitology, 2025)
IntroductionPathogens and parasites play a crucial role in shaping ecological and evolutionary processes, influencing the behavior, physiology, and survival of their hosts across diverse ecosystems. Despite their taxonomic and functional diversity, non-passerine birds remain underrepresented in pathogen/parasite ecological research, providing an opportunity to explore how their unique life histories influence host-parasite dynamics. Investigating the susceptibility of non-passerines to infections, particularly in relation to physiological stress indicators such as heterophil-to-lymphocyte (H/L) ratios and microhematocrit levels, offers valuable insights into the complex interplay between health state, environmental conditions, and disease dynamics.MethodsWe evaluated the occurrence of haemosporidian parasite (avian malaria) infections (Plasmodium spp. and Haemoproteus spp.) in individuals from six non-passerine bird species – Red-legged Seriema (Cariama cristata), Crested Caracara (Caracara plancus), Yellow-headed Caracara (Daptrius chimachima), Dusky-legged Guan (Penelope obscura), Gray-necked Wood-Rail (Aramides cajaneus), and Tropical Screech Owl (Megascops choliba) – that were admitted to the Wildlife Screening Center in Belo Horizonte, Minas Gerais, Brazil. We assessed whether blood-parasite infection occurrence was associated with hematological parameters (e.g. microhematocrit, H/L ratio), major injuries, age, body condition, season, co-occurrence of Trichomonas spp. infections, and presence of ectoparasites.ResultsOf the 75 individuals analyzed, 37% were infected with haemosporidian parasites (Plasmodium spp. and Haemoproteus spp. combined). Age was a significant predictor of haemosporidian infection, with adults exhibiting higher overall haemosporidian parasite occurrence (both Plasmodium spp. and Haemoproteus spp. together), likely due to age-related chronic infection accumulation or higher mortality among infected juveniles. Also, individuals infected with Haemoproteus spp. only showed elevated H/L ratios, suggesting a physiological response to infection, and were more frequently infected during the rainy season, likely reflecting optimal vector conditions. No significant associations were observed between blood-parasite infection occurrence and other factors such as physical condition, major injuries, co-occurring Trichomonas spp., or the presence of ectoparasites.DiscussionThese findings highlight the importance of considering physiological, environmental, and life-history factors when investigating malaria infections in non-passerine birds. By advancing our understanding of host-parasite interactions in these underrepresented species, this study contributes valuable knowledge to inform conservation, rehabilitation, and wildlife-management strategies for these less-studied birds.